Hyflex Pedagogies: Nurturing teacher presence in multi-modal learning spaces post pandemic [version 2; peer review: 2 approved] - TJ O'Ceallaigh; Emma O Brien; Cornelia Connolly (Routledge Open Research)
The COVID-19 pandemic has led to the demand for new modes of teaching and learning. One such approach is Hybrid-Flexible or HyFlex. Utilising a HyFlex model, teachers teach students at the same time face-to-face (f2f) and synchronously online through video-conferencing software while enabling other students to engage in asynchronous learning. Designing, developing and facilitating multiple modes of participation in HyFlex is a challenging endeavor which calls for specialized pedagogical knowledge, competencies and skills. To date, there is a dearth of literature which explores the pedagogies that integrate physical and virtual learning spaces to successfully support the HyFlex learning environment. One of the most widely adopted pedagogies during the pandemic was the Community of Inquiry (CoI) model which focuses on presence as a concept and how social, cognitive, teacher and emotional presence can support student learning in an online environment. The paper analyses the literature to explore the meaning of presence and CoI in a hyflex learning environment. It explores the role of the teacher in designing the optimum learning environment for students. However the role of presence in a hybrid learning environment has not been explored. This paper argues that teachers need to understand how students exist in learning spaces and how the can be co-present in physical, synchronous and asynchronous spaces to enable them to ensure equitable access and design inclusive hyflex learning environments.